Unraveling Childhood Obesity: A Grounded Theory Approach to Psychological, Social, Parental, and Biological Factors - Georgia Karakitsiou; Spyridon Plakias; Foteini Christidi; Anna Tsiakiri (MDPI AG, 2024)
Childhood obesity is a major medical and public health issue of global interest, which is influenced by a diverse array of factors and carries significant medical and psychosocial implications. Despite the extensive studies that have been conducted to explore the specific issue, the impact of several factors that influence, generate, worsen, and make chronic the phenomenon needs further exploration. This study aimed to construct a grounded theory that includes and connects the psychological, social, parental, and biological factors affecting childhood obesity. Key psychological factors include mental health issues such as depression and emotional eating, while social factors encompass socioeconomic status and cultural influences. Parental factors involve parenting styles and feeding practices, and biological factors relate to genetic predispositions and prenatal conditions. These factors interact in complex ways, highlighting the multifactorial nature of childhood obesity. The study employed a qualitative grounded theory approach, using research articles to achieve a thorough understanding. Qualitative analysis of the articles was conducted using Atlas.ti 24.0 software. Twenty-five research articles were required to reach theoretical saturation. The analysis resulted in 336 codes that were grouped into seven broad categories and twenty-four different subcategories. Through the construction of the theoretical framework, it was recognized that obesity in minors is a complex and multifactorial issue and that the network of causes and influencing factors covers a broad spectrum ranging from the individual to the family, and subsequently to society at large, which interact with each other.